The Effectiveness of Positive Psychotherapy on Life Expectancy and Psychological Well-Being in Women with Breast Cancer - Karimi, Ramin; Mirzaian, Bahram; Abbasi, Ghodratollah (Applied Family Therapy Journal (AFTJ), 2022)
Aim: The aim of this study was to determine the effectiveness of positive psychotherapy on life expectancy and psychological well-being in women with breast cancer. Method: The research method was semi-experimental with pre-test-post-test design and follow-up with the control group. The statistical population consisted of all female patients between the ages of 20 and 45 with breast cancer who received a definitive diagnosis of breast cancer according to clinical and laboratory examinations by a specialist. Among them, 30 subjects were selected by available non-random sampling method and were randomly assigned to two experimental groups (positive-oriented psychotherapy) and control (15 in each group). Then, the experimental group was treated with positive psychotherapy methods based on Seligman’s (2006) protocol in 10 sessions of 90 minutes (one session per week) and the waiting list group did not undergo any intervention until the end of the follow-up. Data were collected using Snyder’s Life Expectancy Questionnaire (2000) and Ryff Psychological Well-Being Questionnaire (1989) and analyzed by repeated measure analysis of variance using SPSS-22 software. Results: The results showed that positive-oriented psychotherapy affected life expectancy (F=36.35, P>0.001) and psychological well-being (F=13.54, P<0.001) in women with breast cancer. Conclusion: As a result, health professionals can use any method along with other treatment methods to improve life expectancy, psychological well-being of vulnerable groups, including breast cancer patients.